2011
DOI: 10.1093/humrep/der015
|View full text |Cite
|
Sign up to set email alerts
|

Fibroids not encroaching the endometrial cavity and IVF success rate: a prospective study

Abstract: BACKGROUND The impact of fibroids, not encroaching the endometrial cavity, have on the rate of success of IVF is still controversial. Recent meta-analyses suggest a detrimental effect of intramural lesions but not subserosal lesions. However, they also emphasize the need for further evidence. In order to elucidate this, we designed a prospective cohort study to compare the rate of success of IVF in women with and without fibroids. METHODS Exposed women were those with asymptomatic intramural or subserosal fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 17 publications
2
45
0
2
Order By: Relevance
“…We stated as clinically relevant a relative increase in diameter of 30%. Based on an expected mean 6 SD diameter of the fibroids in our population of 22610 mm [10], the total number of patients to be enrolled was of about 50 women (25 cases and 25 controls).…”
Section: Methodsmentioning
confidence: 99%
“…We stated as clinically relevant a relative increase in diameter of 30%. Based on an expected mean 6 SD diameter of the fibroids in our population of 22610 mm [10], the total number of patients to be enrolled was of about 50 women (25 cases and 25 controls).…”
Section: Methodsmentioning
confidence: 99%
“…Hormones of the hypothalamic-pituitary-thyroid (HPT) axis, triiodothyronine (T 3 ), thyroxine (T 4 ), and thyroid-stimulating hormone (TSH), play an important role in the development of the central nervous system [1], and regulate the metabolism and function of various neurotransmitters [2,3,4], their receptors, second-messengers [5], and gene expression [6]. Evidence for the interaction between serotonin (5-hydroxytryptamine, 5-HT) and thyroid hormones originates mostly from the experimentally induced hypothyroid state in animals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the interaction between serotonin (5-hydroxytryptamine, 5-HT) and thyroid hormones originates mostly from the experimentally induced hypothyroid state in animals [3]. Decreased 5-HT [7, 8] and increased 5-hydroxyinoleacetic acid [9] concentrations were observed in neonatal and adult hypothyroid rats, suggesting an increased 5-HT turnover [7, 10], while T 3 administration to hypothyroid animals normalized 5-HT turnover to normal values [10].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that "future efforts should be aimed to identify the subgroup of women" in whom the fibroid can increase risk. However, like others, they do not advise as to how the authors should identify these patients other than by size and location [23].…”
Section: Management Of Intramural Myoma or Ivf: Which Comes First?mentioning
confidence: 90%
“…Somigliana et al concluded in a recent prospective study that in asymptomatic patients with intramural fibroids smaller than 5 cm not invading the cavity, the results were not affected [23]. They concluded that "future efforts should be aimed to identify the subgroup of women" in whom the fibroid can increase risk.…”
Section: Management Of Intramural Myoma or Ivf: Which Comes First?mentioning
confidence: 99%